A Neolithic Child Burial from Ciemna Cave in Ojców National Park, Poland - Valde-Nowak, Paweł; Stefański, Damian; Szczepanek, Anita (Archaeopress Archaeology, 2018)
This paper describes a newly discovered child burial found in course of a new research project in the main chamber of the Ciemna Cave. Anthropological investigation showed that the skeleton belongs to a fetus that died in the perinatal period. The body was buried in a shallow pit with no grave goods included. The radiocarbon date of the skeleton links it to the Neolithic settlement, most probably to the Baden Culture
il. ; 29 cm